A Development-Oriented IS Evaluation Approach: Case Demonstration for DSS - Miah, Shah J; Debuse, Justin; Kerr, Don (Australasian Journal of Information Systems, 2012)
Information systems (IS) development research needs a broader conceptual lens for evaluating IS design qualities. Most conventional IS evaluation approaches are focused on narrow objectives, such as the process and content rather than the development process as a whole. This paper describes a qualitative evaluation of a new approach that extends evaluation strategies to incorporate development phases, specifically within decision support systems (DSS) development. The conceptual approach is based on a mental model from the design science research paradigm and evaluates DSS development at various design checkpoints. This paper also describes qualitative findings on the applicability of the conceptual approach in a socio-technical design context.